2019
DOI: 10.24917/20845596.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Struktura czynnikowa wdzięczności. Wstępne badania adaptacyjne nad skalą SGRAT-PL

Abstract: Celem niniejszego artykułu jest prezentacja wyników pilotażowych badań adaptacyjnych nad skróconą (16-itemową) wersją skali GRAT. W badaniach pilotażowych udział wzięło 124 respondentów w wieku 20–50 lat (M = 33,55, SD = 5,84). Narzędzie służy do oceny poziomu wdzięczności traktowanej jako dyspozycja jednostki do doświadczania tej emocji. W badaniach użyto polskiej wersji kwestionariusza wdzięczności SGRAT-PL, skali empatii Davisa – IRI oraz ankiety z metryczką na temat zmiennych … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Still, it was decided to test its relation with conditions typical on the spectrum. The hypothesis put forward was supported by research, the results of which showed that gratitude is associated with, among other things, higher quality of life (Tomaszek Lasota, 2019), self-esteem, and relations with other people as well as lower levels of depression (Davis et al, 2016). Thus, individuals exhibiting higher levels of autistic conditions may be characterized by lower self-esteem compared with individuals from the general population (Hull et al, 2017), taking into account their risk of developing depressive symptoms (Hull et al, 2019a) leads to the conclusion that the quality of life of young adults with elevated conditions typical of autism spectrum conditions (exceptionally high severity of autistic conditions) is reduced.…”
Section: Discussionmentioning
confidence: 93%
“…Still, it was decided to test its relation with conditions typical on the spectrum. The hypothesis put forward was supported by research, the results of which showed that gratitude is associated with, among other things, higher quality of life (Tomaszek Lasota, 2019), self-esteem, and relations with other people as well as lower levels of depression (Davis et al, 2016). Thus, individuals exhibiting higher levels of autistic conditions may be characterized by lower self-esteem compared with individuals from the general population (Hull et al, 2017), taking into account their risk of developing depressive symptoms (Hull et al, 2019a) leads to the conclusion that the quality of life of young adults with elevated conditions typical of autism spectrum conditions (exceptionally high severity of autistic conditions) is reduced.…”
Section: Discussionmentioning
confidence: 93%
“…Gratitude was measured using the Gratitude, Resentment, and Appreciation Scale-Short Form [43] in the Polish adaptation [71]. The GRAT-S is a multidimensional tool designed to measure dispositional gratitude.…”
Section: Gratitudementioning
confidence: 99%